Service Learning in teacher training: Children’s Literature from a Gender Perspective - Rodríguez-Olay, Lucía; García-Sampedro, Marta; Avello Rodríguez, Roberto (Journal of Learning Styles, 2022)
This article describes a research performed with some Faculty of Teacher Training students participating in an innovation project, in which, through a Service-Learning proposal, the gender stereotypes present in some Children’s and Young People’s Literature texts are approached. The aims of the research focus on knowing students´ perceptions and satisfaction degree during the implementation of the project, and additionally, if the experience has helped them to improve their teaching and teamwork skills. The research follows a mixed paradigm in which an ad hoc questionnaire and a semi-structured interview have been applied. The quantitative sample is made up of ninety-four students, being fifteen the final number of interviewees. The results show students´ favourable perception, as well as a high degree of satisfaction with the project. The students also consider that the project has helped them improve their teaching and teamwork skills. The results obtained coincide with other previous research on Service-Learning implementations in tertiary education. During these Service-Learning experiences, students are able to live through real work environment and develop their teaching skills while increasing their interest in project contents.